Ventriculoatrial shunts as an alternate therapy in patients with normal pressure hydrocephalus refractory to ventriculoperitoneal shunts: A Case series - Vivian Hagerty (Elsevier, 2022)
Introduction: Normal Pressure Hydrocephalus (NPH) is a prevalent neuropsychiatric disorder characterized by Hakim’s triad: Dementia, gait disturbance, and urinary incontinence in the setting of ventriculomegaly. Ventriculoperitoneal (VP) shunting is largely considered the definitive therapy for NPH. A significant limitation with VP shunts is their rate of failure, which is especially evident in the setting of increased intra-abdominal pressure (IAP). Methods: We retrospectively analyzed the successful placement of ventriculoatrial (VA) shunts in two patients with NPH and increased IAP secondary to high BMI. We assessed outcomes based on improvements in fluency and mentation, patient-reported decreases in urinary frequency, and Tinetti-test assessments for gait. Results: Both patients presented with short term memory loss, urinary incontinence, and shuffling gaits. Lumbar punctures performed in the hospital improved their symptoms, and VP shunts were placed with no improvement in gait or cognition. As both patients had high BMIs, we felt the shunts were not performing optimally due to high intraabdominal pressures and converted the VP shunts to VA shunts. This intervention finally provided long-lasting symptom relief at six- and ten-month follow-up, respectively. Conclusions: The diversion of fluid performed by shunt therapy for NPH is dependent on a distal pressure lower than the patient’s intraventricular pressure. Overweight and obese patients may have elevated IAP of great clinical significance for VP shunt placement, and this variable merits consideration when neurosurgeons select which distal cavity is most appropriate for their NPH patients.